P-208 Combined oncology and palliative care clinics; working in parallel (part 1). Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Gibbins, Jane; Benham, Beccy; Broadbent, Anna; Mader, Amman; Campbell, Carolyn; Newman, Rachel; Stevens, Deborah; Palmer, Joanne
Abstract : Background: Early Specialist Palliative Care (SPC) introduced to patients with advanced lung cancer has recently been proven to enhance quality-of-life and improve survival. Combined Oncology and Palliative Care Clinics (COPCC) have been carried at Royal Cornwall Hospital Trust for over two decades, to enable patients to be reviewed by palliative care consultants (PCC) whilst attending the Oncology Centre; enabling the two specialities to run in parallel to improve patient care. The aims of this project were to explore the types of patients seen and content of consultations. Methods: A retrospective review of the current PCC consultation letter of 150 consecutive patients reviewed between 01/2016–06/2016. Data collected by three medical students. Results: Of the 150 patients, 49% had on-going/planned palliative oncological options (POO), 20% optimal supportive/symptom control (SSC), 18% radical treatment and 13% treated with curative intent. 75% had stable disease, 23% deteriorating and 2% in their last month of life. The main focus of the consultation was symptom control (95%), followed by discussions around aims of palliative/oncological treatment (71%). For patients who were considered POO or SSC (n=104), 66% were referred/known to the community SPC nursing team. The median number of consultations per patient was 2.9, and patients were known to the service for up to five years and two months. Conclusion: COPCCs appears to facilitate collaborative working between disciplines to enable optimal symptom control, information sharing and forward planning to patients attending oncology clinics. Unsurprisingly, PCC focus on symptom control and early referral to SPC services in the community. Many patients are seen when they are 'stable' suggesting the service is proactive in approach. COPCCs remove the need for a 'referral' to SPC, and allows patients to be seen who perhaps wouldn't otherwise be referred to SPC.